The New Edifice of Unity Church, Oak Park, Illinois : Frank Lloyd Wright, Architect, descriptive and historical matter by Dr. Rodney F. Johnnot, pastor,. - Woodard, Charles S.; Johnnot, R.F.; Wright, Frank Lloyd (Illinois : The New Unity Church Club, 1961)
plannen en uitleg over de "Unitarian Universalist Church" in Oak Park
Adlib record nr. 530002749
Engels
boek
Keywords: Wright, Frank Lloyd; modernisme; Verenigde Staten van Amerika